DEMOCRATIC ATTITUDES STUDENTS THROUGH IMPROVED METHOD ROLE PLAYING LESSON IN CIVICS - AWIRIA, AWIRIA (Universitas Islam Negeri Raden Intan Lampung, 2018)
TThe purpose of this study was to determine how the application of the method to play to increase the students' democratic attitudes. The method of this study was as action research in the classroom with mc Taggart model done in two cycles. Each cycle consisted of planing, implementing the action, observing, and reflecting. Data collection used questionnaire. Which was valid and reliable observation of implementation of role playing method, field notes, and photographs of activities. The result of this study shows that there is an increase of students democratic attitudes through aplication of role playing method, where the students democratic attitudes and observation of reaching 73.73%, 77,77% in teachers aspect, 55,5% in students aspect in cycle one and 78,86% students democratic attitudes in cycle two, 100% in teachers and students aspect on cycle two. The implication of this study is that the use of role playing method can improve students democratic attitudes because they can learn to have willingness crities, respect others, be responsible, and give priority to consensus in decision making.